Pengaruh Influencer dan Religiusitas Terhadap Brand Switching Behavior pada Generasi Z di Kota Bengkulu - Niken Oktavia; Herlina Yustati; Badaruddin Nurhab (Universitas Muhammadiyah Surabaya, 2026)
The development of social media has increased the role of influencers in shaping Generation Z’s consumption behavior, particularly in the highly competitive cosmetics industry. On the other hand, religiosity represents a value-based factor that potentially influences consumers’ decisions to engage in brand switching. This study aims to analyze the effects of influencers and religiosity on brand switching behavior among Generation Z in Bengkulu City, both partially and simultaneously. The study adopts a quantitative approach with a causal associative research design. Data were collected through questionnaires distributed to 100 Generation Z respondents and analyzed using multiple linear regression with the assistance of SPSS version 18.The results indicate that influencers have a positive and significant effect on brand switching behavior. Religiosity also has a positive and significant effect on brand switching behavior. Simultaneously, influencers and religiosity significantly influence brand switching behavior, with an Adjusted R Square value of 42.3%. These findings suggest that brand switching behavior among Generation Z is influenced not only by digital social factors but also by religious value considerations such as halal awareness and ethical consumption. The results of this study are expected to serve as a reference for formulating marketing strategies that align with the characteristics and values of Generation Z.